Evaluation of a Health Education Intervention to Improve Parental Knowledge and Attitudes About Chronic Stress and Depression Among Head Start Families. Issue 2 (March 2023) - Guerrero, Alma D.; Herman, Ariella; Teutsch, Carol; Dudovitz, Rebecca
Background . Chronic stress and depression disproportionately affect families experiencing poverty, and likely contribute to disparities in early childhood developmental outcomes. Developing strategies to address chronic stress and depression may help mitigate these disparities. Early Head Start (EHS) and Head Start (HS) programs provide an important platform to address the disproportionate burden of stress and mental health issues experienced by EHS/HS families. However, few low-literacy, broad, scalable interventions improve parents' knowledge and attitudes around these topics. Objectives . We examined parents' knowledge and attitudes regarding stress and depression before and after a train-the-trainer (TTT) intervention delivered to 28 EHS/HS agencies across the United States. Methods . Following a TTT workshop, 18 agencies chose to deliver the stress training to 1, 089 parents and 5 chose to deliver the depression training to 670 parents. Participating parents completed paper assessments at baseline and 3 months following the training. Paired T-tests and chi-square analyses tested whether responses significantly improved over time. Results . At baseline, 37.2% of parents reported feeling stressed most of the time and 13.4% reported feeling depressed most of the time. Following the trainings and reinforcement activities, parents' knowledge, attitudes and self-reported behaviors significantly improved, including willingness to seek help for depression, avoidance of negative health-risk behaviors and utilization of healthy stress management practices. At follow up, 18.6% of parents reported feeling stressed most of the time and 11% reported feeling depressed. Conclusion . Findings suggest this low-literacy TTT approach is potentially a promising health promotion intervention with broad dissemination potential.